Blocking endothelial TRPV4-Nox2 interaction helps reduce ROS production and inflammation, and improves vascular function in obese mice. (August 2021) - Gao, Mengru; Han, Jing; Zhu, Yifei; Tang, Chunlei; Liu, Liangliang; Xiao, Wang; Ma, Xin
Abstract: Obesity induces inflammation and oxidative stress, and ultimately leads to vasodilatory dysfunction in which Transient receptor potential vanilloid type 4 (TRPV4) and Nicotinamide Adenine Dinucleotide Phosphate Oxidase (Nox2) have been reported to be involved. However, little attention has been paid to the role of the TRPV4-Nox2 complex in these problems. The purpose of this study was to figure out the role of the TRPV4-Nox2 complex in obesity-induced inflammation, oxidative stress, and vasodilatory dysfunction. Using fluorescence resonance energy transfer and immunoprecipitation assays, we found enhanced TRPV4 and Nox2 interactions in obese mice. Using q-PCR, fluorescent dye dihydroethidium staining, and myotonic techniques, we found that obesity caused inflammation, oxidative stress, and vasodilatory dysfunction. Using adeno-associated viruses, we found that enhancement or attenuation of TRPV4-Nox2 interaction altered the vaso-function. Based on these findings, we found a small-molecule drug, M12, that interrupted the TRPV4-Nox2 interaction, thereby reducing inflammatory factors and reactive oxygen species production and helping to restore the vasodilatory function. In summary, our results revealed a new mechanism by which obesity-induced inflammation, oxidative stress, and vasodilatory dysfunction is caused by enhanced TRPV4-Nox2 interactions. Using M12 to interrupt the TRPV4-Nox2 interaction may have anti-inflammatory and anti-oxidative stress effects and help restore vasodilatory function and thus provide a new therapeutic approach to obesity. Graphical abstract: Unlabelled Image Highlights: The interaction between TRPV4 and Nox2 was enhanced in obesity. TRPV4-Nox2 coupling helps regulate ROS production, inflammation and vasodilation. Compound M12 exerts a therapeutic effect by attenuating the TRPV4-Nox2 coupling.